Study of the Characteristics of CLC (Cellular Lightweight Concrete) with the Addition of Rice Husk Ash - Ramadhan, Syahrul; Setiawan, Beny; Rusnedy, Hidayati (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study aims to analyze the effect of adding rice husk ash on the compressive strength of Cellular Lightweight Concrete (CLC) blocks. The research background is based on the need for building materials that are lightweight, environmentally friendly, and possess adequate mechanical strength. Rice husk ash is used as an additive material due to its high silica content and its potential to enhance the bonding between particles in the lightweight concrete matrix. The research method employed is an experimental method with variations in the addition of rice husk ash of 0%, 2.5%, 5%, and 10% by weight of cement. The test specimens were cube-shaped and were tested at the ages of 7, 14, and 28 days in accordance with SNI 8640-2018. The results indicate that the compressive strength increases with both the concrete age and the percentage of rice husk ash addition up to an optimum limit. At the age of 28 days, the highest compressive strength was obtained at the 10% rice husk ash variation, reaching 3.63 MPa, while the 5% variation produced a compressive strength of 3.33 MPa. Compared to lightweight blocks without the addition of rice husk ash, all variations exhibited a significant increase in compressive strength. Based on these results, it can be concluded that the addition of rice husk ash up to 10% is effective in improving the compressive strength of CLC lightweight blocks and meets the requirements for non-structural lightweight blocks.